Come out! : Monatsblatt für sexuelle Variation, Politik und Kultur. (Basel : Arcados Verlag, 1989)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Rheingasse 69, CH-4002 Basel
Duits
Periodiek